Dashboard Monitoring dan History Data Tegangan Listrik AC (Alternating Current) - Marsuki, Marsuki; Wijaya, Alek; Rizal, Syahril; Mukti, Aan Restu (Jurnal Ilmiah Matrik, 2024)
Abstract : The rapid development of information technology (IT) in the modern era has driven innovation, including through the Internet of Things (IoT). IoT technology is now applied to monitor critical infrastructure, including Data Centers. Bina Darma University, a private university in South Sumatra, faces challenges in managing Data Center electricity, such as voltage instability and frequent power outages that often damage equipment. This study uses Action Research to design and implement an IoT-based Monitoring Dashboard that monitors electricity voltage in real-time and is integrated with a Telegram notification system. The results show that this Dashboard effectively converts voltage data into useful information and enables quick responses to electrical incidents, thus enhancing oversight and operational efficiency in Bina Darma University's Data Center.